2019
DOI: 10.1519/jsc.0000000000002340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Judo Training on Bones: A Systematic Literature Review

Abstract: The aim of this study was to provide a systematic literature review on the osteogenic effects of judo (PROSPERO: CRD42016041803). The online search was conducted according to the inclusion criteria: observational studies and clinical/interventional trials in English from inception to June 2016; bone health, mineral density (BMD), diameters, impact force and turnover markers (BTM) outcomes. Thirty-four studies were included and graded for their methodological quality ("fair" quality: 79.4%). The most used asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 85 publications
1
34
0
1
Order By: Relevance
“…The higher aBMD values at the upper limbs in judo participants compared to karate, kung fu and swimming has been debated in the literature in a recent systematic review (30) and the results showed the judo as beneficial sport for site-specific BMD accrual in children and adolescents, including the upper limbs (30). Ito et al ( 27) for example, found significantly higher aBMD for upper limbs in judokas compared to the control group and attributed these results to the movements performed during the practice of the modality and fall techniques.…”
Section: Upper Limbs Abmdmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher aBMD values at the upper limbs in judo participants compared to karate, kung fu and swimming has been debated in the literature in a recent systematic review (30) and the results showed the judo as beneficial sport for site-specific BMD accrual in children and adolescents, including the upper limbs (30). Ito et al ( 27) for example, found significantly higher aBMD for upper limbs in judokas compared to the control group and attributed these results to the movements performed during the practice of the modality and fall techniques.…”
Section: Upper Limbs Abmdmentioning
confidence: 99%
“…However, the core movements of the body do not differ considerably among sports which may justify the similarity between the groups. In contrast, during participation in judo, volleyball and soccer there is a high weight-bearing load (jumps, running, fast short movements, changes of directions and falls on the ground) applied to the core body part and therefore lumbar spine which might improve this skeletal site (8,30,31).…”
mentioning
confidence: 99%
“…Studies show that the regular practice of martial arts and combat sports produce beneficial effects for BMD in adolescents of both sexes [28], this shows that this type of exercise can be adapted for older adults and elderly of both sexes. A systematic review demonstrated that judo can enhance bone mass and metabolism in individuals of all ages and both sexes [29]. Furthermore, the study recommends that break fall techniques should be used in other sports and training regimes to protect against sprains and fractures, especially in the older and senior population with osteoporosis [29].…”
Section: Doi: 1034256/ijpefs2046mentioning
confidence: 99%
“…A systematic review demonstrated that judo can enhance bone mass and metabolism in individuals of all ages and both sexes [29]. Furthermore, the study recommends that break fall techniques should be used in other sports and training regimes to protect against sprains and fractures, especially in the older and senior population with osteoporosis [29]. Study that also assessment QoL indicated that groups who engaged in adapted judo showed less fear of falling and avoidance of daily activities that could lead to falls when compared to resistance training, water aerobics and control groups.…”
Section: Doi: 1034256/ijpefs2046mentioning
confidence: 99%
“…The presence in the professional sports of women in the pre-involution period reveals and updates, for the physiology of age and the sports practice, the functional capacity of female body’s cardiovascular system to adapt to an intense physical activity at such a mature age. It is necessary to take into consideration the osteogenic effects of judo in the female practitioners during the premenopausal and postmenopausal period ( Pogodina & Aleksanyants, 2017 ; Akhmetov et al, 2018 ; Ciaccioni et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%